The Draft National Education Policy 2019 : Do we Really Learn from Past Experiences? - Yadav, Dinesh K. (Voices of Teachers and Teacher Educators, 2019)
This article raises concern regarding lack of action on the recommendations of past policies and issues pertaining to teacher recruitment process. It presents recommendations of the draft NEP 2019 on some specific aspects on role of the teacher recruitment principles and procedures, professional and career development, their governance and management by the administration. It suggests developing a conducive school culture and environment, stressed on relieving teachers from non-teaching activities, emphasis on continuous professional development of teachers and career management to improve school education.